PEMBANTUAN DAN PENYERTAAN (DEELMENING) DALAM KASUS PERKOSAAN ANAK - Agus Setyowati, Ike Indra (Media Iuris, 2018)
Rape is a sexual crime. Rape of children will destroy the future of children as the next generation. Nowadays the rape of children, as well as rape committed by children are getting increased. One of the contributing factors is due to the freedom of the child in accessing any information that can not be monitored continuously by parents. It encourages the children to commit acts that are not in accordance with their age and can not hold their lust. If the action is committed by an individual, it would be easy to identify the perpetrator. The problem occurs when it is committed by group. The case is included in the assistance and involvement in its responsibility. This paper discusses the implementation of the concept of assistance and involvement in cases of child rape that the perpetrator more than one person. In addition, it will analyzes Judge's consideration in the case of child rape on Court Decision Number 24 / Pid.Sus / A / 2012 / PN.Pso and Decision Case No 142/ Pid.Sus/2012/PN.Spg.